HISTORY OF ACTIVE FOREIGN POLICY OF UZBEKISTAN - Jahongir Usmanov Xujaqulovich (Western European Studies, 2024)
This article is about the establishment of the first relations of Uzbekistan with neighboring countries, state visits, mutual agreements in the social, economic, political and cultural spheres, friendly relations and strategic relations
Keywords: friendly; political; economic